دراسة مقارنة لترجمات معاني القرأن الكريم آية الكرسي نموجذجا = Study comparison to translation meaning of the Holy Quran Ayat Al-Kursi - Ahmed Mahmoud, Ragheb Ahmed (Journal of Al-Quds Open University For Research and Studies, 2013)
Study comparison to translation meaning of the Holy Quran Ayat Al-Kursi The study examines the translation of Ayat Al- Kursi in the six most known translations of the Holy Quran, observing the translation in terms of accuracy and consideration; highlighting the disparity between these translations down to trying to devise some judgments about these translations. The study’s original commencement was due to the choice of subject, its importance and issues. It is followed to investigate the seven exposures used in the study and that is the concept, types and controls translation of the Qur'an. Defining translations is the main subject in this study then a simplified explanation of Ayat Al-Kursi finalized by displaying the main theme which is showing the six translations, it’s positives and negatives. The study is then accomplished with a conclusion and recommendations, together with bibliographic references.